2018
DOI: 10.1002/aet2.10312
|View full text |Cite
|
Sign up to set email alerts
|

Coaching for Chaos: A Qualitative Study of Instructional Methods for Multipatient Management in the Emergency Department

Abstract: Background: Busy environments, like the emergency department (ED), require teachers to develop instructional strategies for coaching trainees to function within these same environments. Few studies have documented the strategies used by emergency physician (EP)-teachers within these busy, chaotic environments, instead emphasizing teaching in more predictable environments such as the outpatient clinic, hospital wards, or operating room. The authors sought to discover what strategies EP-teachers were using and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…We embarked upon this investigation to describe and further conceptualize swarming, a new model to improve both efficiency and education in the academic emergency setting. The unique challenge of balancing these priorities in the ED has given rise to multiple innovative teaching strategies, which have been described in previous literature . Correspondingly, the results of our qualitative data reflect a general consensus that swarming improves education.…”
Section: Discussionsupporting
confidence: 78%
“…We embarked upon this investigation to describe and further conceptualize swarming, a new model to improve both efficiency and education in the academic emergency setting. The unique challenge of balancing these priorities in the ED has given rise to multiple innovative teaching strategies, which have been described in previous literature . Correspondingly, the results of our qualitative data reflect a general consensus that swarming improves education.…”
Section: Discussionsupporting
confidence: 78%
“…Endorsement for the use of experiential teaching strategies increased significantly in Core of Discipline and for most techniques was even more strongly endorsed in the final stage of training, Transition to Practice. As clinicians gain more experience they develop more advanced heuristics enabling them to more efficiently flow patients in the ED 17,20,21. This facet is important to factor in when trying to teach flow and efficiency to trainees 14.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic survey was made in Google Forms (Mountainview, CA, USA) was created based on findings from a previous research study undertaken by Chan et al17 which identified different flow and management teaching strategies that are employed in the ED (see Data Supplement S1, Appendix S1 [available as supporting information in the online version of this paper, which is available at http://onlinelibrary.wiley.com/doi/10.1002/aet2.10429/full], for details). The survey was a 21‐item questionnaire that encompassed five different subgroups of teaching techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…first-impression vs. direct search for a diagnosis) rather than any actual domain of accuracy or efficiency (Ilgen et al, 2013). Furthermore, given the variety of educational approaches to multi-patient care in the ED (Chan et al, 2019), this domain of critical thinking may be difficult to encapsulate into a single variable. Peters et al noted that clinical reasoning is highly contextual and even social, interactions for which this game did not provide (Peters et al, 2017).…”
Section: Critical Thinking / Multi-tasking Measuresmentioning
confidence: 99%